Modelling the Dynamics of Cow-Calf Dyadic Behavior - Toledo, Luciandra Macedo de; Fernandes, Thayna Barcelos; Rodrigues Paranhos da Costa, Mateus Jose [UNESP]; Ambrosio, Luis Alberto (Igi Global, 2018)
The dynamics of the first suckling is critical for the formation of the complex cow-calf dyad system, where interactions occur among animals and natural and anthropic environments. In this study, the system dynamics method was applied to build conceptual and computational models to better understand the dynamics of dyadic behavior and its interactions with the environment. The model showed that dyadic behavior is manifested by reinforcing feedback loops in which the calf stimulates the cow's maternal functions, which in turn results in caring stimuli towards the calf. Moreover, ecological factors affect the performance of the animals' behavioral system by influencing the rate of direct events for both, cow and calf. The cow-calf dyad model can be used in silico experiments involving animal behavior, which allows computational verification of dynamic ex-ante hypotheses in vivo experiments, thus reducing costs and honoring the ethical principle of minimizing the experimental use of animals.
Keywords: Beef Cattle; Dyad; Ecological Factors; First Suckling; In Silico Experiment; Maternal Care; Simulation; System Dynamics